Quantitative myocardial tissue characterization by cardiac magnetic resonance in heart transplant patients with suspected cardiac rejection - Miller, Robert JH (Clin Transplant, 2019)
Distinct histopathologic changes occur in acute cellular rejection (ACR), antibody mediated rejection (AMR), and biopsy negative rejection (BNR). Cardiovascular magnetic resonance (CMR)-based myocardial tissue characterization can be used to quantify these changes. We assessed T1, T2 and extracellular volume fraction (ECV) by CMR in patients with sub-types of rejection. T1, T2 and ECV were quantified at the mid-ventricular level and compared between patients with and without rejection. The association between quantitative tissue characteristics and the combined outcome of death, re-transplantation, heart failure hospitalization, or myocardial infarction was evaluated with a Cox-proportional hazards model. In 46 patients, mean age 53.3 ± 13.7 years, 71.7% male, at a median of 7.4 years from transplant, average myocardial T1 was increased in BNR compared to no rejection (1057 vs 1012 msec, p=0.006). Average myocardial T2 was elevated in all types of rejection, p<0.05. In a cox-proportional hazards model, higher T2 values were associated with an increase in the combined clinical outcome (adjusted HR 1.21, 95% CI 1.06 – 1.37, p=0.004) after adjusting for left ventricular mass index. Myocardial tissue characteristics are abnormal in all subtypes of rejection and abnormal T2 quantified by CMR provides additional prognostic value.